Functional Polymers as Innovative Tools in the Delivery of Antimicrobial Agents - Umile Gianfranco Spizzirri (MDPI AG, 2022)
Ubiquitous microorganisms such as bacteria, viruses, algae, and fungi induce several infectious diseases, representing crucial health challenges worldwide, due to increased antimicrobial resistance, high antimicrobial cost and adverse effects [...]